Factitious disorder - T. I. Mikulovich (Military Medicine, 2026)
The article describes the symptoms of mental disorder called simulation. It is shown that in patients in clinical picture it is not just a deliberate simulation, but а way to get rid of the exhressed anxiety, which they themselves are unable to cope with. Certain (specific) parallels with obessive-compulsive disorder are performed.